Development of BISAWA (Bingo Aksara Jawa) Media Assisted by Pop Up Book for Teaching Javanese Script Reading to Upper Grade Students - Lilik Ma'rifah; Nur Hanifah Insani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to develop BISAWA (Bingo Aksara Jawa) learning media assisted by Pop Up Book for teaching Javanese script reading to upper grade students. The research method used is Research and Development proposed by Sugiyono through four stages, namely potential problems, data collection, product design, and design validation. Data collection was obtained through interviews and questionnaires, then analyzed using descriptive qualitative and quantitative approaches. Product validation was carried out by material validators to assess learning content and media validators to assess media quality. Based on the results of the material validation test getting a score of 81.3% and the media validation test getting a score of 91.1%, both validators stated that this product is "very feasible" to be used for learning media to read Javanese Script. BISAWA (Bingo Aksara Jawa) media assisted by Pop Up Book is expected to support the learning process of Javanese language, provide a good stimulus for students, improve students' ability to read Javanese script, and assist teachers in delivering varied Javanese script materials. Thus, this media can be utilized to improve the reading skills of elementary school students' Javanese script material.